Distribusi Pergerakan Penumpang Pesawat Udara Di Pulau Jawa Menggunakan Model Furness - Gunawan Gunawan; Dedet Hermawan Setiabudi; Bagus Wahyu Utomo (Institut Teknologi Dirgantara Adisutjipto, 2022)
The movement needs that always increases will cause some problems, especially people are heading to the same destination of the certain area at the same time. To reduce the problems caused by the increase in the number of movements, it is necessary to analyze the future distribution of aircraft passenger movements. The research model is the distribution of aircraft passenger movements in Java Island using the Furness model. In this case, it is found that the Furness model is the best method because have a standard deviation and mean absolute percentage error to the smallest. It could be concluded that the Furness model is more accurate when compared to the Gravity Model (DGCR) with tanner obstacle function in estimating the distribution of movements in 2025 in Java Island